Analysis of delays and cost overruns of road construction projects in the Colombian Caribbean Region - Canales, Fausto A. (2023)
Construction projects are constantly threatened by delays and cost overruns that might compromise their viability. Th us, identifying the leading causes of these issues based on the experience of experienced professionals is essential to planning and reducing these risks. Th is research evaluates the frequency and severity of variables causing delays and cost overruns in Colombian Caribbean Region road projects. Th e nine causes studied in this research were defined through a literature review, preliminary discussion and a pilot test. A survey directed to 42 road construction engineers allowed the authors to characterise these professionals’ perceptions regarding the frequency and severity of these variables in terms of delay and cost overruns, with a confidence level of 80%. Statistical analyses were applied to the results of the survey to establish which variables generate the most significant impacts when building roads and related works in the Colombian Caribbean Region.